Ischemic Posterior Circulation Stroke: A Review of Anatomy, Clinical Presentations, Diagnosis, and Current Management - Nouh, Amre; Remke, Jessica; Ruland, Sean (Frontiers in Neurology, 2014)
Posterior circulation strokes represent approximately 20% of all ischemic strokes (1, 2). In contrast to the anterior circulation, several differences in presenting symptoms, clinical evaluation, diagnostic testing, and management strategy exist presenting a challenge to the treating physician. This review will discuss the anatomical, etiological, and clinical classification of PC strokes, identify diagnostic pitfalls, and overview current therapeutic regimens.